Governance aspects for the development of smart and sustainable cities - Armando Cordeiro Fraga, Antonio; Magda Vasconcelos de Souza, Cilene; Luiz Alves, Jose (Seven Editora, 2023)
The search for sustainable development has required cities to adopt an innovative style of collaborative governance to design public policies, aimed at improving the quality of life of citizens, ensuring economic growth without compromising future generations. This article aims to demonstrate and evaluate the indicators and data on the ranking of smart cities in relation to the governance factor and its connection with public policies. For a better understanding, a conceptual analysis on sustainability will be presented, making a literature review, referencing the main concepts that make up sustainable development. The method used was documentary and bibliographic research, followed by the analysis of secondary data information obtained from the Connected Smart Cities (CSC) website. In the results section, the ranking related to the governance axis was analyzed in the following aspects: first, referring to the ranking of the top 10 smart cities in Brazil; then, the 10 cities considered smart in the Northeast region of Brazil were analyzed and, thirdly, the cities classified as smart in the State of Pernambuco. The concepts and analyzes obtained in this research demonstrated the search for a sustainability model that incorporates the idea of ​​the urgency of transforming the environmental capacity, associated with the human capacity to sustain itself, through actions of the public power, organizations and society transforming the way cities act by providing the addition of smart cities. first referring to the ranking of the top 10 smart cities in Brazil; then, the 10 cities considered smart in the Northeast region of Brazil were analyzed and, thirdly, the cities classified as smart in the State of Pernambuco. The concepts and analyzes obtained in this research demonstrated the search for a sustainability model that incorporates the idea of ​​the urgency of transforming the environmental capacity, associated with the human capacity to sustain itself, through actions of the public power, organizations and society transforming the way cities act by providing the addition of smart cities. first referring to the ranking of the top 10 smart cities in Brazil; then, the 10 cities considered smart in the Northeast region of Brazil were analyzed and, thirdly, the cities classified as smart in the State of Pernambuco. The concepts and analyzes obtained in this research demonstrated the search for a sustainability model that incorporates the idea of ​​the urgency of transforming the environmental capacity, associated with the human capacity to sustain itself, through actions of the public power, organizations and society transforming the way cities act by providing the addition of smart cities. cities classified as smart in the State of Pernambuco. The concepts and analyzes obtained in this research demonstrated the search for a sustainability model that incorporates the idea of ​​the urgency of transforming the environmental capacity, associated with the human capacity to sustain itself, through actions of the public power, organizations and society transforming the way cities act by providing the addition of smart cities. cities classified as smart in the State of Pernambuco.The concepts and analyzes obtained in this research demonstrated the search for a sustainability model that incorporates the idea of ​​the urgency of transforming the environmental capacity, associated with the human capacity to sustain itself, through actions of the public power, organizations and society transforming the way cities act by providing the addition of smart cities. DOI: 10.56238/pacfdnsv1-061